2013
DOI: 10.1016/j.trsl.2012.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Translating the basic knowledge of mitochondrial functions to metabolic therapy: role of L-carnitine

Abstract: Mitochondria play important roles in human physiological processes, and therefore, their dysfunction can lead to a constellation of metabolic and nonmetabolic abnormalities such as a defect in mitochondrial gene expression, imbalance in fuel and energy homeostasis, impairment in oxidative phosphorylation, enhancement of insulin resistance, and abnormalities in fatty acid metabolism. As a consequence, mitochondrial dysfunction contributes to the pathophysiology of insulin resistance, obesity, diabetes, vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(75 citation statements)
references
References 100 publications
3
65
0
3
Order By: Relevance
“…Omnivores obtain most L-carnitine from their diet. In cells, carnitine functions in the transport of fatty acids into mitochondria (65).…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Ementioning
confidence: 99%
“…Omnivores obtain most L-carnitine from their diet. In cells, carnitine functions in the transport of fatty acids into mitochondria (65).…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Ementioning
confidence: 99%
“…11 Carnitine is a natural and essential vitamin-like substance that plays an essential role in myocardial energy production at the mitochondrial level. 12 It transfers long chain fatty acids across the inner mitochondrial membrane for b-oxidation and abnormalities in carnitine metabolism are thought to contribute to cardiac dysfunction. 13,14 Many studies have demonstrated a beneficial effect of levo-carnitine (LC) supplementation in various types of cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that L-carnitine may have to be administered at doses that achieve supra-physiological concentrations in plasma and target tissues to fully exploit its pharmacologic potential. 12,13 This study found that Fc and Tc levels in non-medicated patients undergoing HD were lower than those in the control group. The Fc, Ac, and Tc levels of patients increased significantly after 1 g L-carnitine was administered intravenously.…”
Section: Discussionmentioning
confidence: 71%